Current State of the East Kazakhstan Transportation and Logistics Complex - Madiyarova, E.S.; Gabdullina, L.B.; Zeynullina, A.Zh. (KU publ., 2020)
Object: study of the current state and development priorities of the transport and logistics complex of the East Kazakhstan region. Methods: the theoretical basis of the research is the works of domestic and foreign scientists-economists on the development of the transport and logistics complex, legislative and regulatory acts of the Republic of Kazakhstan. The information base of the research is based on the data of the statistics Committee of the Ministry of economy of the Republic of Kazakhstan and the results of the authors' research. The methodological basis of the research is a systematic approach, abstract-logical, economic-statistical, monographic methods of studying economic processes. Findings: this article presents the results of the analysis of the socio-economic development of the East Kazakhstan region and the transport complex of the region. The analysis revealed the main problems of development of the transport and logistics complex of the East Kazakhstan region, including limited logistics and technical capabilities of carriers, underdeveloped infrastructure, lack of developed transport and logistics centers, warehouses and terminals, lack of qualified specialists, low quality of service. Conclusions: the main factors affecting the transport and logistics complex of the East Kazakhstan region are studied. As a result of the research, priority measures for the development of the transport and logistics complex of the region are proposed, including modernization of transport logistics, construction of large warehouse complexes and improvement of production infrastructure, creation of an effective network of transport communications and use of innovative technologies in the transport and logistics complex.
Шығыс Қазақстан облысының көлік-логистикалық кешенінің қазіргі жағдайы
Современное состояние транспортно-логистического комплекса Восточно-Казахстанской области
Keywords: transport complex; logistics; macroregion; regional economy; transport network; transport hubs; cargo terminals; transit; foreign trade; cargo and passenger transportation